The Influence of Memorable Tourism Experiences on Place Attachment and Behavioral Intentions: A Study of Museum Visitors in Bandung, Indonesia - Muhtan Dewan Muhtadin; Heri Puspito Diyah Setiyorini (Faculty of Economics and Business, University of Mataram, 2026)
This study examines the influence of Memorable Tourism Experiences (MTEs) on Place Attachment and Behavioral Intentions among visitors to the Geological Museum of Bandung, Indonesia. A quantitative approach was employed using a survey of museum visitors selected through purposive sampling. Data were collected using a structured questionnaire adapted from established scales and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that memorable tourism experiences significantly enhance visitors emotional attachment to the destination and positively influence their future behavioral intentions. Visitors who perceive their museum experiences as enjoyable, meaningful, novel, and educational are more likely to develop stronger emotional bonds with Bandung and demonstrate favorable behavioral responses, including revisit intentions and positive recommendations. The study highlights the strategic role of memorable experiences in strengthening museum attractiveness and fostering long-term visitor relationships. These findings contribute to museum tourism literature and provide practical implications for enhancing visitor experience management.